Law Enforcement Against Minors as Narcotics Dealers in Pohuwato Regency - Mohammad Ishak (Estudiante Law Journal, 2019)
Abstract: This study aims to analyze law enforcement against minors as narcotics traffickers in Pohuwato Regency. The process of law enforcement on children uses a different application method from other legal models. because the suspect who is brought before the investigator's desk is a person who is still underage or not yet legally competent. Based on this, the researcher aims to analyze the application of law to minors as narcotics traffickers. This study uses an empirical method by including interview data along with official data sourced from the Indonesian National Police, especially the Pohuwato Regional Police. justice and balance for the perpetrators of the crime and the victims themselves. Factors that become obstacles in the application of the law against narcotics committed by minors are divided into two, namely internal factors and external factors. With the diversion method based on a justice or judicial approach based on deliberation or restorative justice , it is hoped that legal development in Indonesia will prioritize more humanistic laws so that Indonesian law does not seem rigid. Keywords: Diversion, Narcotics, Restorative Justice